A new crystalline daidzein-piperazine salt with enhanced solubility, permeability, and bioavailability - Meng, Jiacheng; Qiu, Chenxu; Lu, Chenyue; He, Xin; Zhao, Xinghua (Frontiers in Pharmacology, 2024)
To overcome the poor solubility, permeability, and bioavailability of the plant isoflavone daidzein (DAI), a novel salt of DAI with anhydrous piperazine (PIP) was obtained based on cocrystallization strategy. The new salt DAI-PIP was characterized by powder X-ray diffraction (PXRD), differential scanning calorimetry (DSC), thermogravimetric analysis (TGA), Fourier-transform infrared (FT-IR) spectroscopy, and optical microscopy. The results showed that the maximum apparent solubility (Smax) of DAI-PIP increased by 7.27-fold and 1000-fold compared to DAI in pH 6.8 buffer and water, respectively. The peak apparent permeability coefficient (Papp) of DAI-PIP in the Caco-2 cell model was 30.57 ± 1.08 × 10−6 cm/s, which was 34.08% higher than that of DAI. Additionally, compared to DAI, the maximum plasma concentration (Cmax) value of DAI-PIP in beagle dogs was approximately 4.3 times higher, and the area under the concentration-time curve (AUC0-24) was approximately 2.4 times higher. This study provides a new strategy to enhance the dissolution performance and bioavailability of flavonoid drugs, laying a foundation for expanding their clinical applications.